En quête d’une vérité oblique : les œuvres de Pierre Bordage au miroir de leurs artefacts mythographiques - Simon Bréan (ReS Futurae, 2019)
Pierre Bordage frequently puts science fictional artifacts as epigraphs to every chapter in his novels. This paper will try and show that, in Bordage writing, all the functions of these artifacts are encompassed in a broader approach to mythical thinking, so as to emulate how mythographic writing can be lively and elusive. By studying several novels (Les Guerriers du silence, Abzalon, Orchéron, Les Fables de l’Humpur, La Fraternité du Panca), we will be able to identify more efficiently what it means to write in a mythical way.